PENGARUH POSISI MATAHARI TERHADAP PENENTUAN AWAL WAKTU SALAT PERSPEKTIF ILMU FALAK - JULI PRASETIA PANCA PUTRI KAMISWIDARYANI; Nur Aisyah; Muh. Anis (HISABUNA: Jurnal Ilmu Falak, 2023)
The discussion in this article is about the perspective of astronomy in determining the beginning of prayer times. The main issues in this article are: 1.) How is the influence of the position of the sun in determining prayer times? 2.) What is the role of astronomy in determining prayer times? This article is classified as library research, data is collected by quoting, adapting, and analyzing representative literature that has relevance to the problems discussed, then reviews, and concludes. After holding a discussion about the Analysis of the Effect of the Position of the Sun on the Early Determination of Prayer Times from the Astrological Perspective, the authors can conclude that the determination of the beginning of prayer times is not always the same every day so that it will change depending on the position of the sun and solar data. Likewise in knowing the end of the prayer time that has been determined. The method used to determine the beginning of the prayer time in this study was the calculation method (reckoning). For this reason, it is very important to study more deeply about astronomy, especially regarding the determination of the beginning of prayer times because every day the position of the sun will be different so that the prayer times change differently. The implication of the research in this article is that the author hopes that the government, astronomy experts, Islamic organizations, especially students, will continue to study more deeply the books of astronomy written by contemporary scholars in order to broaden their understanding of the early determination of prayer times. regarding the early determination of prayer times to the community, especially in remote areas so that people also know how to determine the early prayer times and understand that prayer times are not always the same every day. Keywords: Astrology, Sun, Prayer Times